1D–2D hybrids as efficient optoelectronic materials: a study on graphitic carbon nitride nanosheets wrapped with zinc oxide rods. Issue 13 (5th March 2018) - Sett, A.; Das, D.; Banerjee, D.; Ghorai, U. K.; Das, N. S.; Das, B.; Chattopadhyay, K. K.
Abstract : Zinc oxide (ZnO) nanorods (NRs) wrapped with graphitic carbon nitride (GCN) nanosheet (NS) hybrids have been synthesized by a simple chemical process. Abstract : Zinc oxide (ZnO) nanorods (NRs) wrapped with graphitic carbon nitride (GCN) nanosheet (NS) hybrids have been synthesized by a simple chemical process. The as-prepared samples are characterized by X-ray diffraction, field emission scanning electron microscopy, high resolution transmission electron microscopy, Fourier transformed infrared spectroscopy, UV-Vis spectroscopy and photoluminescence spectroscopy. The images obtained from the transmission electron microscopic study and the existence of C–N stretching modes as observed from Fourier transform infrared spectroscopy confirm the successful attachment of GCN NSs onto the ZnO NRs. It is seen that hybrid samples show broad photoluminescence (PL) emission with enhanced defect related emission along with a quenching effect due to the charge transfer mechanism. The results have been explained by taking into consideration the three different types of electron transitions occurring within the type-II band structure of the hybrid samples. Moreover a study on the conductivity of the samples is carried out under dark conditions and also under ultraviolet (UV) light irradiation. It is observed that the hybrid samples show significantly improved conductivity under both dark and UV irradiated conditions. The absorbance of the samples in the UV range shows better conductivity under UV conditions as compared to dark conditions.